A Review of African Americans’ Beliefs and Attitudes About Genomic Studies: Opportunities for Message Design - Scherr, Courtney L.; Ramesh, Sanjana; Marshall-Fricker, Charlotte; Perera, Minoli A. (Frontiers in Genetics, 2019)
Precision Medicine, the practice of targeting prevention and therapies according to an individual’s lifestyle, environment or genetics, holds promise to improve population health outcomes. Within precision medicine, pharmacogenomics (PGX) uses an individual’s genome to determine drug response and dosing to tailor therapy. Most PGX studies have been conducted in European populations, but African Americans have greater genetic variation when compared with most populations. Failure to include African Americans in PGX studies may lead to increased health disparities. PGX studies focused on patients of African American decent are needed to identify relevant population specific genetic predictors of drug responses. Recruitment is one barrier to African American participation in PGX. Addressing recruitment challenges is a significant, yet potentially low-cost solution to improve patient accrual and retention. Limited literature exists about African American participation in PGX research, but studies have explored barriers and facilitators among African American participation in genomic studies more broadly. This paper synthesizes the existing literature and extrapolates these findings to PGX studies, with a particular focus on opportunities for message design. Findings from this review can provide guidance for future PGX study recruitment.